2010
DOI: 10.1159/000279753
|View full text |Cite
|
Sign up to set email alerts
|

Bromocriptine and Dopamine Mediate Independent and Synergistic Apoptotic Pathways in Pituitary Cells

Abstract: Dopamine (DA) agonists are the primary treatment choice for prolactinoma, effectively suppressing prolactin expression and reducing tumour size. However, the intracellular pathway(s) through which either DA or its agonists impact on proliferation or lead to tumour shrinkage are incompletely understood. To identify the mediators in the apoptotic cascades after DA or DA agonist challenges we used a well-characterized model system, the rodent somatolactotroph cell line GH3. In these cells, we show that apoptosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 81 publications
3
33
0
Order By: Relevance
“…However, the DA-and BC-mediated apoptotic pathways converge to activate the terminal caspase-caspase-3. Coincubation experiments in these cells reinforced and extended these findings where we observed a synergistic increase in apoptotic end points (12).…”
supporting
confidence: 79%
See 4 more Smart Citations
“…However, the DA-and BC-mediated apoptotic pathways converge to activate the terminal caspase-caspase-3. Coincubation experiments in these cells reinforced and extended these findings where we observed a synergistic increase in apoptotic end points (12).…”
supporting
confidence: 79%
“…Although this transporter represents an attractive alternate mechanism a recent study from our laboratory, using this same model system, namely, the rodent pituitary cell line GH3, reached a different conclusion. In this case, we showed that both DA and BC elicits an apoptotic response in these cells in the absence of a either a D2R or a DAT (12). Moreover, characterization of the intracellular apoptotic pathways engaged by these drugs show them to be distinct.…”
mentioning
confidence: 66%
See 3 more Smart Citations